Birds of Costa Rica - Howell, Steve N. G. (Princeton field guides., 2023)
"A state-of-the-art illustrated field guide to the birds of Costa Rica. Costa Rica is among the most popular birding destinations in the world, with a breathtaking diversity of neotropical birdlife and stunningly beautiful habitats ranging from shady mangrove swamps to mist-enshrouded mountaintops and verdant rainforests. Birds of Costa Rica is the essential illustrated pocket guide to this biologically rich country. It covers all regularly occurring bird species found in the region and features facing-page plates and text that make field identification easy. Concise species accounts describe everything from size and distribution to voice, habitat, and status. This compact guide also features progressive taxonomy and a wealth of color range maps. Covers more than 800 species of birds found in Costa Rica, includes more than 200 superb color plates, and features concise species accounts, facing-page plates and text, and up-to-date range maps. Its compact size and field-friendly layout make it the ideal travel companion for any birder"--